The impact of childbirth on women's sexuality and methods of treating its disorders - Igor Matkowski; Paula Bigos; Konrad Dendys; Jan Bieniasz; Wojciech Kuźnicki; Piotr Potyrała (Kazimierz Wielki University, 2023)
Postpartum sexual disorders can significantly impact individuals and their partner relationships, affecting a considerable percentage of women, with reduced libido being the most common symptom. Factors such as breastfeeding, postpartum depression, and communication issues with partners increase the risk of experiencing these disorders. This review aimed to explore scientific reports on the frequency, contributing factors, and treatment options for postpartum sexual disorders. The analysis was conducted by reviewing literature available in PubMed. The mode of delivery (natural or cesarean) does not significantly differ in its impact on postpartum sexual disorders. Non-pharmacological treatments encompass psychotherapy, from which mindfulness-based cognitive is the most effective and physical exercises. Engaging in regular physical exercises contributes to enhanced sexual experiences, notably in terms of sexual arousal and offers other health benefits. Moreover, Kegel exercises have been demonstrated as a method to increase sexual satisfaction. Medications used to treat libido dysfunction include flibanserin, bremelanotide, and bupropion. For women experiencing depression and sexual dysfunction, antidepressants with a lesser impact on sexual function may be considered. Vaginal dryness can be effectively addressed with moisturizing gels, globules, and lubricants. When considering pharmacotherapy, it is essential to evaluate the severity of symptoms, potential side effects for both the woman and her child being breastfed, and psychological discomfort. Physicians play a vital role, as women with sexual disorders may find it challenging to express their concerns. Partner support is crucial in improving a woman's sexual life.